PENGARUH ARUS KAS BEBAS, LABA AKUNTANSI, DAN KEBIJAKAN DIVIDEN TERHADAP RETURN SAHAM (Studi Empiris pada Perusahaan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Budianto, Budianto (ABDI EQUATOR, 2024)
The capital market plays a crucial role in maintaining economic stability within a country by serving as a funding source for companies and offering investment opportunities to the public through various financial instruments such as stocks. Stocks are particularly appealing as a financial instrument because they not only provide companies with the chance to raise funds from investors but also offer investors the opportunity to gain attractive returns. One sector believed to have profit potential is the banking sub-sector. The banking sub-sector is part of the stock market sector involved in financial activities, including services like deposits, lending, and investments. The purpose of this research is to examine the relationship between free cash flow, accounting profit, and dividend policy on stock returns for companies operating in the banking sub-sector listed on the Indonesia Stock Exchange. The data used in this study were obtained from 12 purposively sampled companies out of a total of 47 in the banking sub-sector during the period from 2018 to 2022. The research employs a quantitative associative method, utilizing multiple linear regression analysis with the assistance of SPSS version 26. The findings of this study indicate that, individually, free cash flow, accounting profit, and dividend policy do not have a significant impact on stock returns. These results suggest that investors may not be able to discern positive signals conveyed by companies through free cash flow, accounting profit, and dividend policy